DESAIN KURSI KERJA BERKAITAN DENGAN UNSUR KESEHATAN TUBUH & PENINGKATAN KWALITAS KERJA - Dyan Agustin, Niniek Anggriani (Jurnal Rekayasa Perencanaan, 2005)
In every day life, human cannot be separated from the activities that had close relationship with the fulfilling of the needs of human. Human life needs rooms which full with tools that suitable with the needs like lamps, air conditioner, chair and other furniture. For that, it needs a study and the right design so human can feel comfortable. Chair is a tool of main room arrangement wich function, even in a simple occation can be use without notice other elements, so the present of chairs in a room is a must.Working chair is one of many kind of chairs that often use especially when we are at work. This research has purpose to make a most comfortable chair that can be use for work, by analizing the activities that occur. Whilst later, will be reach the design of the chair that comfortable and beautiful, so the health of the body and the quality of work can be increase.Key word: Design , Working Chair , Ergonomic.